First record of Macaca (Cercopithecidae, Primates) in the Middle Pleistocene of Greece. Issue 162 (January 2022) - Konidaris, George E.; Athanassiou, Athanassios; Panagopoulou, Eleni; Harvati, Katerina
Abstract: In this article, we describe an almost complete macaque mandible from the Middle Pleistocene locality Marathousa 1 in the Megalopolis Basin of southern Greece. The mandible belonged to a male individual of advanced ontogenetic age and of estimated body mass ∼13 kg. Comparative metric analysis of its teeth permits its attribution to the Barbary macaque Macaca sylvanus, a species that was geographically widely distributed in Western Eurasia during the Plio-Pleistocene. The dental dimensions of the Marathousa 1 macaque fit better within the variation of the Early Pleistocene M. s. florentina and the Middle to Late Pleistocene M. s. pliocena rather than with the extant representative M. s. sylvanus . Moreover, principal component analysis reveals a better match with M. s. pliocena . However, because no clear-cut diagnostic criteria have been defined to differentiate these European fossil subspecies, we attribute the Marathousa 1 specimen to M. s. cf. pliocena, in agreement with the chronology of the locality. Previously known only from the Early Pleistocene of Greece by some isolated teeth, this is the first record of Macaca in the Middle Pleistocene of the country and one of very few in the eastern sector of the peri-Mediterranean region. We discuss the presence of macaques in the paleolake environment of Marathousa 1, as well as their predation risks from both carnivores and hominins present at the locality.